The PARPscore system using poly (ADP-ribose) polymerase (PARP) family features and tumor immune microenvironment in glioma - Cheng Zhang; Juan Feng; Xia Zhou; Jie Zhang; Chuming Tao; Hongwei Zhou (Discover Oncology)
Abstract The immune response plays a pivotal role in tumor progression and therapy. However, the influence of protein PAR polymerases (PARPs) modifications on cell infiltration within the tumor microenvironment (TME) remains insufficiently understood. In this study, the Clinical and RNA sequencing data we performed a comprehensive analysis of PARPs modification patterns, exploring their associations with TME cell infiltration were acquired from the Cancer Genome Atlas (TCGA) and Chinese Glioma Genome Atlas (CGGA) database. To quantify PARPs modification in individual tumors, we developed a novel metric, the PARPscore, derived using principal component analysis. Our findings revealed three distinct PARPs modification patterns, each correlated with unique TME infiltration characteristics and tumor immunophenotypes. These patterns demonstrated predictive value for various clinical parameters, including inflammation stage, tumor subtypes, TME matrix activity, genetic variations, and patient prognosis. Notably, the high PARPscore subtype exhibited features of stromal activation and reduced immune infiltration, indicative of a non-inflamed, immune-excluded TME phenotype, and was associated with poorer survival outcomes. Conversely, lower PARPscore subtypes corresponded to substantial therapeutic benefits and improved outcomes in two independent immunotherapy cohorts. This study underscores the critical role of PARPs modification in shaping the diverse and dynamic TME. By delineating tumor-specific PARPs modification patterns, we provide valuable insights into TME complexity and its implications for immunotherapy.